Iatrogenic Radial Artery Injuries: Variable Injury Patterns, Treatment Times, and Outcomes. (January 2021) - Kim, Doris; Arbra, Chase A.; Simon Ivey, J.; Burchett, Philip; Gonzalez, Gilberto; Herrera, Fernando A.
Background: The radial artery is commonly accessed for arterial blood sampling, invasive blood pressure monitoring, and vascular access for cardiac catheterization. Iatrogenic radial artery injury is a rare complication with potentially devastating outcomes. The purpose of our study was to identify the timing of these injuries and define a treatment algorithm.Methods: A retrospective chart review of all patients with iatrogenic radial artery injuries were identified between the years 2008 and 2018. Patient demographics, mechanism of injury, interventions, and outcomes were recorded.Results: A total of 18 patients were identified with iatrogenic radial artery injury over a 10-year period. Fifty percent of these resulted from arterial line cannulation, and 50% occurred after transradial cardiac catheterization. Thirty-three percent resulted in radial artery pseudoaneurysm (RAP), and 66% had acute radial artery thrombosis (RAT). Eleven of the 18 patients underwent operative intervention. Of the 12 patients with RAT, 4 were treated with systemic anticoagulation for 3 months. All patients with RAP who were surgically treated had resolution of symptoms on follow-up evaluation. Of the patients with RAT, 2 had persistent sensorimotor deficits after treatment, and 1 patient had multiple necrotic fingers requiring amputation.Conclusion: Radial artery injuries are an uncommon but potentially devastating complication of common invasive procedures resulting in thrombosis, pseudoaneurysm, or overt hand ischemia. The treatment options vary depending on presenting symptoms.